Leader Humor and Organizational Citizenship Behavior: Mediation Mechanism of Leader-Member Exchange - Fitri Yunita; Rizqa Anita (Yayasan Education Al Aqsho Modern, 2022)
This study aims to analyze the influence of the leader's humorous behavior and organizational citizenship behavior and the mediating role of the leader-member exchange. The location of this research was carried out in one of the government agencies in the city of Pekanbaru - Riau. While the time of the study was carried out from April to May 2021. The source of this research data is employee respondents at one of the government agencies in the city of Pekanbaru - Riau. With 39 respondents as the research sample. Data analysis techniques are descriptive analysis, convergent and discriminant validity tests and reliability tests, with PLS Structural Equation Modeling (SEM) analysis which is operated through the SmartPLS program. The results of this study show that Leader Humor Behavior has a positive effect which can encourage employees to be involved in Organizational Citizenship Behavior (OCB) in one of the government agencies in the city of Pekanbaru - Riau and Leader-Member Exchange (LMX) is able to mediate the relationship between Leader Humor Behavior and Organizational Citizenship Behavior (OCB) for employees in one of the government agencies in the city of Pekanbaru – Riau.